(untitled) (Scientific journal of the Fergana State University, 2024)
This article examines the analysis and effectiveness of the pedagogical and psychological aspects of teaching “Chemical Technology” on the basis of interdisciplinary communication in the training of specialists working in the chemical industry and the formation of their worldview.